Relationship Between Parenting Styles and Bullying Behaviours of Learners in Primary Schools in Mbita Sub County, Kenya - Aloka, Leah Achola (JOOUST, 2017)
Bullying is the most common form of violence in our schools and studies show that it makes schools unsafe places for children and has contributed to the perception that some schools are not safe anymore. Bullying behaviors have been reported among primary school learners in Mbita Sub-County. Reports from the Mbita Sub County Education office indicate that bullying reported cases among primary school learners had escalated between 2009 to 2014. These behavior problem interfere with learners, teachers, and the school environment. It has been found out that, children who are bullied at school have significantly poorer mental health than others, and are also more likely to experience mental illness as adults. The purpose of the study was to investigate the relationship between parenting styles and bullying behaviours of primary school learners in Mbita Sub County, Kenya. The study objectives were: to investigate the relationship between authoritative parenting style and bullying behaviours among primary school learners; to determine the relationship between authoritarian parenting style and bullying behaviours among primary school learners; to find out the relationship between Permissive parenting style and bullying behaviours among primary school learners; and to establish the relationship between uninvolved parenting style and bullying behaviours among primary school learners. The study was based on Diana Baumrind's parenting styles theory and the Problem Behaviour Theory. A Concurrent Triangulation design within the mixed methods approach was adopted in the study. A multistage sampling was used to select the 324 learners in 10 schools. The Parenting styles and bullying behaviours questionnaires were administered to collect quantitative data. Interview schedules were also used to collect qualitative data from 10 primary school teachers, 10 parents and 10 head teachers both selected using simple random sampling techniques. Content validity of the research instrument was enhanced through expert judgment by university lecturers and also a pilot study using learners not under the study. Reliability of questionnaires was determined by internal consistency method in which coefficient alpha of 0.881 was reported. Trustworthiness of qualitative data was also be ensured. Qualitative data was analyzed using thematic analysis while inferential statistics such as Pearson product moment correlation and regression analysis were used to analyze quantitative data with the aid of SPSS version 22. The findings revealed a plausible significant (r = -.645) negative relationship between authoritative parenting style and bullying behaviour among primary school learners; a considerable positive correlation (r = .510) between bullying behaviour of learners and the authoritarian parenting style; a weak positive (r = .203) correlation between between permissive parenting style and bullying behaviour among the learners and a significant negative (r =.639) relationship between uninvolved parenting style and bullying behaviours among primary school learners. The study recommended that guidance and counseling teachers should understand varied parenting styles of learners and adopt appropriate therapy techniques that could assist modify bullying behaviours.
Keywords: Parenting Styles; Bullying Behaviours; Mbita Sub-County